Pengaruh Motivasi, Budaya Organisasi, Produktivitas Dalam Peningkatan Kinerja Pegawai Di Uptd PJU (Penerangan Jalan Umum) Kota Parepare - Esse, Andi; Rina; Syam, Andi Hendra (Jurnal Online Manajemen ELPEI, 2025)
This study aims to determine how the influence of Work Motivation, Organizational Culture and Work Productivity on the performance of employees of UPTD PJU Parepare City. This study is a quantitative study with research subjects at the UPTD PJU Parepare City office. Sampling in this study used the census sampling technique, which is a sample determination technique when all members of the population are used as samples, so that the sample used in this study involved all 96 employees. Data collection used a questionnaire which was then analyzed using path analysis. The results of this study indicate that on path or sub-structural 1, namely Work Motivation, Organizational Culture and Productivity have a significant effect on Performance both simultaneously and partially. The results of path or sub-structural 2 are that Work Motivation, Organizational Culture and Productivity have a significant effect on work performance both simultaneously and partially.